2017
DOI: 10.1177/0961000617742445
|View full text |Cite
|
Sign up to set email alerts
|

Career progression of female librarians in public university libraries in Ghana

Abstract: The growing interest in gender issues and female employment has generated a number of studies and the library and information profession has not been excluded from this interest in promoting female equality in employment. This study investigates the career patterns of practising professional female librarians in six selected public university libraries in Ghana, in order to establish the enhancers and inhibitors they experience in their career progression. The study, conducted with a survey method, adopted the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 40 publications
0
1
1
Order By: Relevance
“…The women librarians have the required education, management skills, contribution to librarianship as a profession and contribution to knowledge, even though their emotional intelligence and special aptitude are low. This finding negates the finding of Adjah and Van Der Walt (2017) which studied career progression of female librarians in public university libraries in Ghana and found that "female librarians were unable to meet requirements for promotion in their various public university libraries, which has resulted in very slow progress in their careers and even stagnated careers".…”
Section: Discussioncontrasting
confidence: 61%
“…The women librarians have the required education, management skills, contribution to librarianship as a profession and contribution to knowledge, even though their emotional intelligence and special aptitude are low. This finding negates the finding of Adjah and Van Der Walt (2017) which studied career progression of female librarians in public university libraries in Ghana and found that "female librarians were unable to meet requirements for promotion in their various public university libraries, which has resulted in very slow progress in their careers and even stagnated careers".…”
Section: Discussioncontrasting
confidence: 61%
“…Furthermore, there is a moderate positive correlation between occupation and gender, suggesting gender-based differences in occupational distribution in library operations. Akpebu-Adjah and Van-der-Walt [31] noted similar trends, emphasizing the impact of gender on career choices and opportunities in the library sector. Educational background shows a positive correlation with gender, indicating gender differences in educational attainment within the library profession.…”
Section: Discussionmentioning
confidence: 73%
“…15 The independent and collective effects of demographic variables and self-efficiency among women academic Librarians working in tertiary institutions in Nigeria. The job opportunities and professional achievements, and career patterns have been intricately associated with the publishing contributions (Adjah and Walt, 2017) 16 . The continued growth of women library professionals has been seen through the achievement of higher education and professional qualifications, contributing to the hierarchy of jobs in all types of libraries at all levels, and the differences in job satisfaction of university library professionals (Marasinghe and Wijayaratne, 2018).…”
Section: Career Advancement Opportunities and Technology Adaptationmentioning
confidence: 99%